THE EFFECT OF DIFFERENT FEED ON THE GROWTH RATE OF Artemia salina - Tampubolon, Kristanti; Effendi, Irwan; Tanjung, Afrizal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2020)
Artemia salina is a natural feed that is widely used in fish and shrimp hatcheries due to of its good nutritional content. This research was conducted in August 2019. This study aims to determine the effect of different types of feed on the growth rate of A. salina on a laboratory scale. The method used in this study was an experimental method that uses a completely randomized design (CRD) 1 factor with 3 level namely, cornstarch (A), wheat (B) and tapioca (C). Water parameters show that the conditions was in good condition with average temperatures ranging from 28.1 - 28.7 oC, the pH 8 and with a salinity of 60 ppt. Body length of A. salina ranged from 5.33 - 82.33 mm, where the body length in level A (cornstarch) was 82.33, level B (wheat) was 54.33, level C (tapioca) was 18, 67 and the control level is 5.33. The results of the ANOVA test for body length increase of A. salina showed p<0.05, that is 0.00. The survival rate of A. salina with different feed ranges from 0.5% - 88.50%, where the survival rate in level A (cornstarch) is 88.50%, level B (wheat) is 3.17%, level C (tapioca) is worth 51.50% and Control level is worth 0.5%. Survival rate in level A (cornstarch) is quite good. Based on ANOVA test, the survival rate between levels showed p<0.05, that is 0.00.